Urban-Rural Disparities in Smoking Prevalence, Consumption, and Indoor Smoking Habits Among Older Adults in Indonesia - Wihatno, Elvianto; Asri, Yuni; Kushayati, Nuris; Parahita, Doxana Putri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Smoking is a major public health concern worldwide and is a leading cause of preventable morbidity and mortality. In Indonesia, smoking rates are among the highest globally; however, little is known about smoking behavior among older adults, particularly across rural and urban settings. This study aimed to examine the prevalence of smoking and its associated factors among older adults in Indonesia, focusing on demographic, socioeconomic, and geographic disparities. A cross-sectional analysis was conducted using data from the Indonesian Health Survey (SKI) 2023, which included 97,339 participants aged 60 years and older. A multi-stage stratified cluster sampling method was employed to ensure representativeness. Smoking behavior, cigarette consumption, and indoor smoking practices were analyzed alongside demographic variables, such as age, sex, education level, marital status, work status, and region. Descriptive statistics and chi-square tests were used, with adjustments for the complex survey design using STATA 15.1. The overall smoking prevalence was 30.98%, with a higher rate in urban areas (17.77%) than in rural areas (13.21%). Daily cigarette consumption was more common than weekly smoking, and 76.23% of smokers reported smoking indoors. Smoking was significantly associated with a lower educational level, employments status, and marital status. Urban residents showed a higher smoking prevalence and consumption pattern than rural residents. This study highlights disparities in smoking behavior among older adults in Indonesia, emphasizing the need for targeted public health interventions. Efforts should focus on reducing indoor smoking, improving access to smoking cessation programs, and addressing socioeconomic factors contributing to smoking behavior, particularly in urban areas